Neonatal Intrathoracic Gastric Volvulus in Marfan's Syndrome - Serradilla, Javier (European J Pediatr Surg Rep, 2018)
We report a 12-day-old male who was admitted with vomiting because of an unusual early complication of Marfan's syndrome (MS): a sliding hiatal hernia. Initial ultrasound showed no stomach at its normal position and the chest X-ray presented an intrathoracic gas bubble with the nasogastric tube inside. An upper gastrointestinal contrast study confirmed the complete herniation of the stomach into the thorax. Via an exploratory laparotomy it was carefully reintroduced into the abdomen, following a hiatal reconstruction. A Thal fundoplication and a gastrostomy were also performed to guarantee its fixation. Although characterized by cardiac/aortic abnormalities, MS should be considered in any infant with hiatal/paraesophageal hernia, which should be repaired early to avoid gastric ischemia/volvulus.